Duodenal follicular lymphomas share common characteristics with mucosa-associated lymphoid tissue lymphomas. Issue 3 (29th June 2007) - Sato, Y; Ichimura, K; Tanaka, T; Takata, K; Morito, T; Sato, H; Kondo, E; Yanai, H; Ohara, N; Oka, T; Yoshino, T
Abstract : Background: Follicular lymphomas occasionally arise in the extra-nodal organs and are frequently found in the duodenum. They are often localised tumours with multiple polyps around the ampulla of Vater. Aims: To examine a IgH/bcl-2 hybrid gene and VH gene to investigate the nature of the lymphoma cells and how they differ from nodal follicular lymphomas and MALT lymphomas. Methods: Of 40 patients reported previously, 35 with duodenal follicular lymphoma were studied in detail with respect to clinicopathological characteristics. Results: 37/40 patients were in clinical stage I (n = 30) or stage II (n = 7). Clonal immunoglobulin gene rearrangement was detected in 53.3% of examined cases, and rearrangement of IgH/bcl-2 gene at the major break point was detected in 27% of cases. Three of 8 examined cases were VH4 (38%); 2 out of them were VH4-34. As VH4 deviation is one of the common characteristics of MALT lymphomas and 2/3 were identical, duodenal follicular lymphomas have a similar aetiology to MALT lymphomas. Clinical course was also similar to that of MALT lymphomas. Conclusions: Results suggest that duodenal follicular lymphomas have intermediate characteristics of MALT lymphomas and nodal follicular lymphomas.